Effects of introducing an online community in a crowdsourcing contest platform. (17th June 2022) - Ye, Jonathan (Hua); Jensen, Matthew
Abstract: Crowdsourcing platform owners and operators constantly search for ways to improve contestant performance. One novel proposal for improving performance is the introduction of an online community to the crowdsourcing contest platform. However, research regarding the potential benefits of an online community on such platforms is unclear. Furthermore, prior research often assumes the single dimensionality of prior experience, whose impacts on crowdsourcing performance are also inconclusive. Building on knowledge collaboration and cognitive diversity research, we model the direct effects of introducing an online community on contestant performance and the moderating effects of the amount of experience and experience diversity. Leveraging a natural quasi‐experiment in a large crowdsourcing contest platform, we collected 24 months of contestant data to test our hypotheses. Our propensity score matching and difference in differences analysis demonstrated that contestants' performance (winning contests and crowdsourcing income) increases significantly with the presence of an online community. Additionally, the positive effect of an online community on performance is more pronounced for contestants with less experience and those with more diverse experience. Our findings provide insights into the causality of incorporating an online community and inform community investment decisions for crowdsourcing contest platforms.